2013
DOI: 10.1590/s0102-67202013000200011
|View full text |Cite
|
Sign up to set email alerts
|

Percepção corporal e cirurgia bariátrica: o ideal e o possível

Abstract: The body perception seems to comply with own body size, even after weight loss. As longer postoperative period, the participants were more aware of the real possibilities of weight loss. There were signs of dissatisfaction with the body size and shape, mainly in the PO-1 and PO-2, which can lead to frustration and little use of the benefits of the surgery for health and quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
(19 reference statements)
0
3
0
1
Order By: Relevance
“…Moreover, Ribeiro et al [34] have shown body shape expectations also tend to get more realistic with ongoing time. Therefore, long-term studies are needed to evaluate goals and achievements in relation to QOL in obesity surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Ribeiro et al [34] have shown body shape expectations also tend to get more realistic with ongoing time. Therefore, long-term studies are needed to evaluate goals and achievements in relation to QOL in obesity surgery.…”
Section: Discussionmentioning
confidence: 99%
“…It's also necessary to consider the psychosocial aspects. Women have been suffering a great deal with the obesity stigma of thinness in the sense that it falls on them the beauty stereotype socially constructed and perpetuated in society, demanding an idealistic pattern of beauty 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Lately, the Stunkard Scale has been increasingly implemented to evaluate body image perception and body dissatisfaction in different populations [10][11][12]. To assess body image perception, participants are asked to indicate the silhouette of the Stunkard scale, which mostly resembles their current body figure.…”
Section: Introductionmentioning
confidence: 99%